Mateuszowa Ewangelia cudów (Mt 8–9)– przekład alternatywny - Bardski, Krzysztof (Warszawskie Studia Teologiczne, 2018)
In our article we propose a new translation of Matth. 8–9 into Polish. After discussing other Polish translations of the text (in the footnotes), we suggest alternative options that would intensify the expressivity of the narrative and stress the semantic aspects that have been neglected in former Polish translations but seem to be important in the context of the postmodern reception of the biblical text.